Integrasi Materi Pembelajaran Iman, Islam, dan Ihsan dalam Upaya Mencegah Dekadensi Moral di Era Digital - Sita Isna Malyuna; Masruroh Lubis (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Technological developments have not only positive impacts, but also negative ones, one of which is deviant behavior and even moral decadence. The formulation of learning materials is of course very important to become a source of student understanding regarding the dangers of moral decadence. This study gacor5000 aims to analyze the integration of faith, Islam and ihsan learning materials in Islamic religious learning at Al-Wafi Islamic Boarding School. This study uses a qualitative research method based on phenomenology. Informants in this study were teachers of Islamic religious education, and students participated in the lesson. Data collection was carried out using observation techniques, interviews and documentation studies. The results of the study revealed that the background of the integration of learning materials was based on students' understanding which tended to be partial, besides that an understanding of faith, Islam and ihsan was needed in realizing good human beings with good morals. These three things, namely faith, Islam and ihsan can be used as fences or signs for each individual so that they are not easily drawn into things that are contrary to religion or prevailing norms. The integration of the material is realized by making it into one discussion, and not implemented partially.